1997
DOI: 10.3354/meps150075
|View full text |Cite
|
Sign up to set email alerts
|

Trophic relations in the subarctic North Pacific ecosystem:possible feeding effect from pink salmon

Abstract: ABSTRACT-Year-to-year variations in biomass of phytoplankton (surface chlorophyll a concentration) and macrozooplankton (wet weight obtained by NORPAC net operation above 150 m), and abundance of pink salmon (catch per unit effort of pink salmon) from 1985 to 1994 in the subarctic North Pacific in summer were studied. After 1989, phytoplankton biomass and pink salmon abundance showed corresponding yearly patterns, whereas the pattern shown by macrozooplankton biomass was always the inverse of that shown by phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 1 publication
3
65
0
Order By: Relevance
“…Perhaps grazing on small microzooplankton by large microzooplankton and metazoans are reducing grazing pressure on small algae by limiting small microzooplankton biomass? These trophic cascades have been described in oceanic ecosystems (Shiomoto et al, 1997;Calbet et al, 2001). If top down control on microzooplankton were in effect, low abundance and biomass of microzooplankton in the bloom would be expected.…”
Section: Microzooplankton Grazing Biomass and Abundancementioning
confidence: 75%
“…Perhaps grazing on small microzooplankton by large microzooplankton and metazoans are reducing grazing pressure on small algae by limiting small microzooplankton biomass? These trophic cascades have been described in oceanic ecosystems (Shiomoto et al, 1997;Calbet et al, 2001). If top down control on microzooplankton were in effect, low abundance and biomass of microzooplankton in the bloom would be expected.…”
Section: Microzooplankton Grazing Biomass and Abundancementioning
confidence: 75%
“…The data of Smith and Vidal (1986) (Table 2) and those of Coyle and Pinchuk (2002b) (Table 3) show that the result is a positive relationship between integrated water temperature and the abundance of copepods available to support juvenile fishes. Models suggest that planktivores can be food limited, as do data on the impact of salmon on the plankton of the subarctic North Pacific (Shiomoto, Tadokoro & Ishida, 1997) and the central Bering Sea (Sugimoto and Tadokoro, 1997). Data indicating that adult pollock are capable of exerting top-down control of their own recruitment support element 4.…”
Section: The Oscillating Control Hypothesismentioning
confidence: 97%
“…Long-term changes in zooplankton abundance, biomass and community structure have been reported at Ocean Station P (Mackas et al 2007) and CalCOFI (Clarke & Dottori 2007) in the eastern North Pacific, and Oyashio region in the western North Pacific (Chiba et al 2006). Information on long-term changes in zooplankton communities in the central North Pacific include annual and regional changes in biomass reported by Sugimoto & Tadokoro (1997, annual changes in biomass reported by Shiomoto et al (1997) and annual changes in abundance and body size of Neocalanus copepods reported by Kobari et al (2003a).…”
Section: Introductionmentioning
confidence: 99%